Cognitive Radio Oriented Wireless Networks 10th International Conference, CROWNCOM 2015, Doha, Qatar, April 21-23, 2015, Revised Selected Papers - Weichold, Mark; Hamdi, Mounir; Shakir, Muhammad Zeeshan; Abdallah, Mohamed; Karagiannidis, George K.; Ismail, Muhammad (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th International Conference on Cognitive Radio Oriented Wireless Networks, CROWNCOM 2015, held in Doha, Qatar, in April 2015. The 66 revised full papers presented were carefully reviewed and selected from 110 submissions and cover the evolution of cognitive radio technology pertaining to 5G networks. The papers are clustered to topics on dynamic spectrum access/management, networking protocols for CR, modeling and theory, HW architecture and implementations, next generation of cognitive networks, standards and business models, and emerging applications for cognitive networks.